The Effect of Sauropus androgynus (L.) Merr. Leaf Flour Supplementation on Growth Performance and Fat Deposition in Broiler Chickens - Siti Rani Ayuti; Dita Ramadhania Putri Sinulingga; Putri Dwi Ningsih; Sugito Sugito; Herrialfian Herrialfian; Mudastsir Mudastsir; Mira Delima (Jurnal Agripet, 2026)
The use of natural feed additives as alternatives to antibiotic growth promoters has gained increasing attention. However, evidence regarding their specific effects on carcass traits and fat deposition in broilers is limited and inconsistent. This study provides new evidence of the role of Sauropus androgynus leaf flour in modulating growth performance and lipid distribution in broiler chickens. The objective of this study was to evaluate the effects of Katuk leaf flour on carcass characteristics and fat deposition. A total of 75 broiler chicks were reared for 28 days and randomly assigned to five dietary treatments, with five replicates per treatment and three birds per replicate: a control diet and diets supplemented with 40, 60, 80, and 100 g/kg of Katuk leaf flour. Data were analyzed using analysis of variance, followed by Duncan’s multiple range test. The results showed that Katuk leaf flour supplementation significantly increased slaughter and carcass weights (P<0.05), whereas the carcass percentage was not affected (P>0.05). Notably, abdominal and breast fat deposition was significantly reduced (P<0.05), indicating improved lipid utilization and more efficient energy partitioning. In conclusion, supplementation with Katuk leaf flour at 80-100 g/kg has strong potential as a natural feed additive to enhance broiler productivity and carcass quality by reducing excessive fat deposition without compromising carcass yield.